Hypoxia Medical Journal
The results of the scientific research carried out in the Laboratory and other scientific units developing the IHT method are published in the "Hypoxia Medical Journal" which has been issued since 1993. The Journal is published in collaboration with the Russian Academy of Medical Sciences in Russian and English. It is edited by the Russian Editorial Board in collaboration with International Advisory Board. The Russian Academy of Medical Sciences (RAMS) supports the new trend in medicine. The president of the Academy V.Pokrovsky is both the editor-in-chief of "Hypoxia Medical Journal" and the chairman of the Scientific Council working under the auspices of "Hypoxia Medical" and RAMS on issues of hypoxia in medicine. Clinical results of the use of IHT and basic developments in this field are presented quarterly in "Hypoxia Medical Journal".